STUDY OF PECULIARITIES OF FORM AND STYLE IN THE DESIGN OF MENSWEAR IN THE XX CENTURY - Navolska, L. V. (Art and Design, 2023)
Purpose: study of evolution in men’s costume form-building, and orderliness of constructional and decorative lines and details based on the visual analysis of its forms development in the XX century, detection and classification of presentation means for creating perspective collections of menswear. Methodology. The research is based on the use of historical and cultural, comparative methods; informational sources and portfolio of modern men’s wear designers have been applied, the results have been synthesized. Theoretical, methodological basis for the investigation is based on scientific and methodological works of experts in history of costume and clothing design, scientific concepts of clothing design theory. Results. Due to the research, the main aspects of form-building processes have been defined providing unity and harmony of menswear and contributing to its relevance in time. In has been specified that a modern men’s suit as a marker of identity and individual visual language requires intensive discussion about the future of men’s fashion. All this requires needs of today’s consumers and their preferences in clothing to be revealed in order to forecast trajectories of development of menswear design subject to the results of work done by fashion designers of the XX century and the present ones. In addition, owing to the research results it has been revealed that the latest men’s fashion is becoming more and more personified, that is why the eclectics of styles, in complete sense of this word remains a perspective area for successful creative activity of modern designers. Scientific novelty. The studies carried out have provided an opportunity to detect the concept of form-making and define the logic of changes in menswear form-building, its ergonomic, constructional and technological aspects. Due to the investigation interrelation between peculiarities of gradual transformation of visual content of the artistic men’s suit in the XX century into the corresponding visualization of a present consumer image has been considered in detail, substantiated and distinguished. Practical significance. Practical importance of the results received lies in modeling form-making processes in menswear, helps to detect and analyze factors which influence the form, define their future relevance. Practical use of the research will facilitate setting trend of active evolution in today’s men’s wardrobe; moreover, it will help educate specialists in the art sector, will become a ground for successful work of designers, fashion-designers and modern clothing manufacturers.